Machine learning Algorithm using classification and regression tress, linear gaussian naive bayes, support vector machines, cart and K-nearest neighbors to aid cancer research firms in data grouping ang better analysis - Rebbecah Ndungi (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2022)
et,1/adil,c.1